State ownership and financial reporting quality: Evidence from natural advantage industries - Boubakri, Narjess; Durnev, Art; Oliveira dos Santos, Igor (Journal of Corporate Finance, 2025)
Using a hand-collected sample of state-owned enterprises and newly privatized firms around the globe, we examine financial reporting quality in natural advantage (substantial oil reserves or mineral deposits) industries. We find that ultimate state ownership tends to deteriorate financial reporting quality. Such a finding tends to occur particularly in countries with low shareholder minority protection, low financial development, high resource extraction intensity, low freedom of the press, collectivist societies, poor government anti-diversion policies, and in resource-dependent countries. Finally, we document that ultimate state ownership in the context of better financial reporting quality is associated with exacerbated capital expenditures, which indicate resource overextraction. Such a finding applies particularly to resource-dependent countries and civil-law countries.